2010
DOI: 10.1037/a0018489
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation and decision making under risk and uncertainty.

Abstract: It is well established that emotion plays a key role in human social and economic decision making. The recent literature on emotion regulation (ER), however, highlights that humans typically make efforts to control emotion experiences. This leaves open the possibility that decision effects previously attributed to acute emotion may be a consequence of acute ER strategies such as cognitive reappraisal and expressive suppression. In Study 1, we manipulated ER of laboratory-induced fear and disgust, and found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
192
4
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(236 citation statements)
references
References 89 publications
(127 reference statements)
11
192
4
9
Order By: Relevance
“…Our study, in conjunction with other work showing effective emotion regulation to diminish susceptibility to cognitive biases (e.g. Heilman, et al, 2010;Sokol-Hessner et al, 2010) suggests that an important component of such learning effects may be learning to more effectively regulate the emotions that are both incidental and integral to high stakes financial decision-making.…”
Section: Discussionsupporting
confidence: 55%
“…Our study, in conjunction with other work showing effective emotion regulation to diminish susceptibility to cognitive biases (e.g. Heilman, et al, 2010;Sokol-Hessner et al, 2010) suggests that an important component of such learning effects may be learning to more effectively regulate the emotions that are both incidental and integral to high stakes financial decision-making.…”
Section: Discussionsupporting
confidence: 55%
“…Angry and frustrated investor's may be more 8 Despite being difficult to control, people regularly make efforts to control their experience of emotions and the effects of those emotions on decision making processes (Gross, 2002). Indeed, it has been shown that an individual's ability to effectively control their emotions has implications for their decision making processes under uncertain conditions (Heilman et al, 2010). While individual differences in degree of emotional regulation likely explain some variance in the behaviors that we explore with this study, our recalibrational model is not a model of individual differences.…”
Section: Introductionmentioning
confidence: 99%
“…These cultural characteristics can have consequences on emotion regulation (Matsumoto, 2006) and may impact not only the scores obtained by consumers on the four dimensions of childlike consumer behavior but also the dimensions themselves. For example, decision-making, which is related to the reality conflict and control of aggression dimensions, is also related to emotion regulation (Heilman, Crişan, Houser, Miclea, & Miu, 2010).…”
Section: Limitationsmentioning
confidence: 99%